Disappearing Rooms The Hidden Theaters of Immigration Law - Castañeda, Michelle (Dissident Acts, 2023)
Michelle Castañeda lays bare the criminalization of race enacted every day in U.S. immigration courts and detention centers in order to reimagine alternatives to the deportation regimes.